2016
DOI: 10.3390/genes7100082
|View full text |Cite
|
Sign up to set email alerts
|

OprD Repression upon Metal Treatment Requires the RNA Chaperone Hfq in Pseudomonas aeruginosa

Abstract: The metal-specific CzcRS two-component system in Pseudomonas aeruginosa is involved in the repression of the OprD porin, causing in turn carbapenem antibiotic resistance in the presence of high zinc concentration. It has also been shown that CzcR is able to directly regulate the expression of multiple genes including virulence factors. CzcR is therefore an important regulator connecting (i) metal response, (ii) pathogenicity and (iii) antibiotic resistance in P. aeruginosa. Recent data have suggested that othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Loss of OprD leads to resistance to carbapenem in clinical isolates and enhanced fitness in animal infection models (Pirnay et al ., ; Wolter et al ., ; Skurnik et al ., ). It has been previously suggested that oprD is regulated at the post‐transcriptional level (Li et al ., ; Ducret et al ., ). PagL encodes a lipid A 3‐O‐deacylase.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Loss of OprD leads to resistance to carbapenem in clinical isolates and enhanced fitness in animal infection models (Pirnay et al ., ; Wolter et al ., ; Skurnik et al ., ). It has been previously suggested that oprD is regulated at the post‐transcriptional level (Li et al ., ; Ducret et al ., ). PagL encodes a lipid A 3‐O‐deacylase.…”
Section: Resultsmentioning
confidence: 97%
“…Several previous studies have examined the regulatory mechanisms controlling the expression of OprD and suggesting a role for Hfq and an sRNA‐based regulatory mechanism. The transcription of the oprD gene is negatively regulated by two metal responsive two‐component systems (CzcRS and CopRS) and this regulatory effect requires the Hfq protein (Ducret et al ., ). Hfq appears to directly facilitate binding of the response regulator CzcR to the promoter of the oprD gene.…”
Section: Discussionmentioning
confidence: 97%
“…The transcript abundance of oprD , encoding a porin responsible for carbapenem uptake (Lynch et al, 1987 ) was 5-fold higher in PA14Δ hfq than in PA14 (Supplementary Table S2 ). It has been previously reported that Hfq negatively controls oprD expression indirectly on the transcriptional and directly on the post-transcriptional level via sRNAs (Ducret et al, 2016 ; Zhang et al, 2017 ), which can explain the increased susceptibility of the hfq deletion strains toward imipenem (Tables 1 , 2 , Supplementary Table S1 ). Moreover, the Hfq-Crc complex appears to repress translation of oprD mRNA directly (P. Pusic, unpublished).…”
Section: Resultsmentioning
confidence: 97%
“…Fe 2+ and Mn 2+ ) or by accumulating others, such as Cu 2+ and Zn 2+ , to intoxicating concentrations (Flannagan et al, 2015;Lopez and Skaar, 2018). On the pathogen side, bacteria have evolved several strategies to survive excess of metal ions, both in the environment (Ducret et al, 2016;Gonzalez et al, 2018) and in contact with phagocytes (Botella et al, 2011). For instance, metal efflux transporters, such as cation diffusion facilitators and P-type ATPases, remove excess ions from the bacterial cytoplasm (Chan et al, 2010;Kolaj-Robin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%